2018
DOI: 10.1038/s41467-018-06339-2
|View full text |Cite
|
Sign up to set email alerts
|

Ancient and modern anticonvulsants act synergistically in a KCNQ potassium channel binding pocket

Abstract: Epilepsy has been treated for centuries with herbal remedies, including leaves of the African shrub Mallotus oppositifolius, yet the underlying molecular mechanisms have remained unclear. Voltage-gated potassium channel isoforms KCNQ2–5, predominantly KCNQ2/3 heteromers, underlie the neuronal M-current, which suppresses neuronal excitability, protecting against seizures. Here, in silico docking, mutagenesis and cellular electrophysiology reveal that two components of M. oppositifolius leaf extract, mallotoxin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…As for (E)-2-dodecenal ( Fig. 5), the importance for mallotoxin binding of R213 outweighs that of W236, as determined using site-directed mutagenesis and TEVC of wild-type and mutant KCNQ2/3 channels (11,41). Interestingly, mutation of human KCNQ2-R213 is associated with benign familial neonatal convulsions (54), and the residue represents a hinge point between the pore module and the VSD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As for (E)-2-dodecenal ( Fig. 5), the importance for mallotoxin binding of R213 outweighs that of W236, as determined using site-directed mutagenesis and TEVC of wild-type and mutant KCNQ2/3 channels (11,41). Interestingly, mutation of human KCNQ2-R213 is associated with benign familial neonatal convulsions (54), and the residue represents a hinge point between the pore module and the VSD.…”
Section: Discussionmentioning
confidence: 97%
“…Voltage-gated potassium (Kv) channels within the Kv channel subfamily Q (KCNQ), also termed the Kv7 subfamily, are sensitive to activation by a range of small molecules, including synthetic drugs, neurotransmitters, and metabolites (9)(10)(11)(12)(13). Kv channels, including the 5 isoforms within the KCNQ (Kv7) subfamily, are composed of tetramers of pore-forming (a) subunits, each consisting of 6 transmembrane segments (S): S1-4 comprise the voltage-sensing domain (VSD), and S5-6 comprise the pore module ( Fig.…”
mentioning
confidence: 99%
“…We also recently found that some plant metabolites can hyperpolarize KCNQ channel activation voltage dependence by binding to an arginine (e.g., R242 in KCNQ3) at the foot of S4, abutting the S4-5 linker (Fig. 5b) [20][21][22][23] . More recently, we found that this arginine also influences GABA binding 23 .…”
Section: Resultsmentioning
confidence: 92%
“…org/. Illustrations of KCNQ structure were based on the X. laevis KCNQ1 cryoEM structure 33 , which we altered to incorporate KCNQ3 residues known to be important for GABA and mallotoxin binding 8,20,21 , followed by energy minimization using the GROMOS 43B1 force field 34 , in DeepView 35 . Thus, X. laevis KCNQ1 amino acid sequence LITTLYIGF was converted to LITAWYIGF, the underlined W being W265 in human KCNQ3.…”
Section: Discussionmentioning
confidence: 99%
“…However, little progress has been made in understanding the analgesic effects of Kv7/M channel openers in gout arthritis pain. Recently, numerous compounds have been reported to activate KCNQ/M channels [28][29][30][31][32]. In particular, retigabine and flupirtine are the best described neuronal M current activators.…”
Section: Discussionmentioning
confidence: 99%